To mix or not to mix in allergy immunotherapy vaccines. Issue 6 (December 2021) - Nelson, Harold S.
Abstract : Purpose of review: European and US allergists generally do not agree on the approach to subcutaneous allergy immunotherapy in patients with multiple allergies. The North American approach is to treat with a mixture that contains all the allergen extracts to which the patient has evident clinical sensitivity, whereas the European approach is to select for treatment the one or at the most two allergens that are clinically most important for the patient. Recent findings: Recent society guidelines continue to recommend these differing practices of treating the polyallergic patient and reviews of prescribing practices indicate these divergent recommendations are followed in Europe and the USA. Summary: The objections by European allergists to the practice by US allergists are that multiallergen immunotherapy leads to dilution of allergens to less than effective doses, that proteases in some extracts can degrade allergens in other extracts, that there is a problem of safety and inability to determine which component extract caused a systemic reaction, and finally that there is alack of convincing studies demonstrating efficacy of multiallergen mixtures. Each of these contentions is addressed.